A educação e as relações com o trabalho na lógica do capital - Silva, Marli da; Cunha, Jorge Luiz da (Linguagens & Cidadania, 2017)
This present text is intended to build a reflective dialogue about themes related to Education and Work. Throughout the text are analyzed questions as: what justifies the social inequality; which the place of belonging of the worker in the current economy; which is the role of education in society; how to configure the idea of competence and quality in the educational context and in the questions of work; which the logic of the current capital. The text is organized into three subtitles, namely: 1 - The Work and the relationship with the processes of formation of the Capital 2 – The Education and qualification paths of Work and Productivity 3 - The Human Capital and the speech built in educational scenario through the ’skills and competencies’.